EDUCATIONAL COMMUNICATION MANAGEMENT IN ORGANIZATIONS - Yahya, Rosnida (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
The character study is one of the types of qualitative research which is often used to complete one of the assignments in higher education. In the biographical model, the thing that is the focus of research is the life as a whole or several phases of the life of an individual that is considered unique, distinctive, interesting, or extraordinary so that it is very worthy of being appointed as qualitative researchEffective communication is the key word for the success of leaders in interactions with members, subordinates or followers. Both formal leaders and informal leaders need to improve their communication skills to support the success of their leadership duties, both as government, political, educational, social leaders and leaders of households and community and religious organizations.Muslim leaders need to explore and practice Qur'anic ethical values in communicating to carry out the function of human caliphate on the surface of the earth to spread prosperity and mercy to all nature. Only with ethical communication can the message conveyed by a leader influence the mindset and behavior of the people towards the pleasure of Allah SWT.